Successful cryoablation of incessant fast-slow atypical atrioventricular nodal reentrant tachycardia in a child with tachycardia-induced cardiomyopathy - Yakup Ergül; Ahmet İrdem; Osman Esen; Alper Güzeltaş (KARE Publishing, 2018)
A 15-year-old female patient presented at the clinic with heart failure (HF). A 12-lead electrocardiogram showed a heart rate of 170 bpm; negative P waves in leads DII, DIII, aVF; and long RP tachycardia (LRPT). Echocardiography demonstrated a shortening fraction (SF) of 20%. An electrophysiology study during tachycardia revealed an atrial-His time of 52 milliseconds and a His-atrial interval of 295 milliseconds. During ventricular entrainment, the postpacing interval-tachycardia cycle length was measured at 225 milliseconds. There was a pseudo V-A-A-V response. These findings confirmed the diagnosis of atypical atrioventricular nodal re-entrant tachycardia (aAVNRT). Successful slow pathway cryoablation was performed with an 8-mm-tip cryocatheter. After 2 weeks, the SF was measured as 34%. During a 2-year follow-up period, no recurrence was observed. In conclusion, fast-slow aAVNRT should be a part of the differential diagnosis of incessant LRPT leading to HF. Cryoablation can be used successfully in cases of aAVNRT.